2010
DOI: 10.1007/s11033-010-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention of cow ghee and soybean oil on expression of cell cycle and apoptosis related genes in normal and carcinogen treated rat mammary gland

Abstract: The present study investigated the effect of cow ghee (clarified butter fat) versus soybean oil on the expression of cyclins A and D1, and apoptosis regulating Bax, Bcl-2 and PKC-α genes in mammary gland of normal and 7,12-dimethylbenz(a)anthracene (DMBA) treated rats. Two groups of 21 days old female rats were fed for 44 weeks diet containing cow ghee or soybean oil (10%). The animals were given DMBA (30 mg/kg body weight) through oral intubation after 5 weeks feeding. Another two groups fed similarly but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…An elevated expression of intratumor cyclin D1 in DMBA control animals emphasizes the central role of this cell cycle regulatory protein in DMBA-induced mammary tumorigenesis in rats. This is in line with previous studies showing overexpression of cyclin D1 in rat mammary gland tumors induced by DMBA [5659]. Similar upregulation of cyclin D1 protein in DMBA-induced early stage mammary carcinogenesis in rats has been reported by several investigators [60, 61].…”
Section: Discussionsupporting
confidence: 93%
“…An elevated expression of intratumor cyclin D1 in DMBA control animals emphasizes the central role of this cell cycle regulatory protein in DMBA-induced mammary tumorigenesis in rats. This is in line with previous studies showing overexpression of cyclin D1 in rat mammary gland tumors induced by DMBA [5659]. Similar upregulation of cyclin D1 protein in DMBA-induced early stage mammary carcinogenesis in rats has been reported by several investigators [60, 61].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, cow ghee (clarified butter oil) fed to rats reduced the incidence of 7,12-dimethylbenz(a)anthracene (DMBA)-induced mammary tumours compared to a diet containing soybean oil [60]. The mechanism appeared to involve a decrease in the expression of cyclins A and D1, Bcl-2 and PKC-a [61]. Here, we have shown that milk fat has greater anti-tumour activity than soybean oil.…”
Section: Discussionmentioning
confidence: 93%
“…The nuclear factor erythroid 2-related factor 2 (Nrf2) is an endogenous antioxidant signaling involved in the regulation of antioxidantoxidative stress balance. The Nrf2 induces the transcription of genes such as HO-1 via antioxidant response element protein [8,9]. Similarly, these inflammatory mediators induce the activation of several inflammatory pathways such as NF-κB, which plays crucial role in the transformation of chronic inflammation to tumor formation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, these inflammatory mediators induce the activation of several inflammatory pathways such as NF-κB, which plays crucial role in the transformation of chronic inflammation to tumor formation [10]. These signaling pathways interact with the several transcriptional factors and alter the cellular growth and differentiation [8,11].…”
Section: Introductionmentioning
confidence: 99%